Comparison between Average Lifetime Earnings of Government and Private School Teachers (Interdisciplinary Research in Education, 2024)
Education equips individuals with skills, enabling them to earn higher incomes than those without such qualifications. However, earnings are influenced by age/experience, indicating a significant connection between education, age, and earnings. The age-earnings profile serves as a tool to understand the lifetime earnings distribution of individuals within specific education groups, aiding in retirement decisions. In this context, the study's objectives are to estimate the average lifetime earnings of government and private school teachers and compare the age-earnings profiles, before and after tax, among these groups. The study, conducted in Kathmandu district, Nepal, focuses on estimating average lifetime earnings and comparing before-and after-tax age-earnings profiles of government and private school teachers. The post-positivism philosophy was adopted, using a cross-sectional survey design with 100 school teachers as the study unit. Results reveal differences in earning patterns between private and government school teachers, indicating that higher education correlates with higher earnings in both settings. Notably, private school teachers earn less than their government counterparts, suggesting disparities in salary facilities between Kathmandu's two types of schools.